Schmuck, R. A. and Schmuck, P. A. (1976). Group Processes in the Classroom. (2nd edition) - Pierog, Rita H. (Canadian Journal of Counselling and Psychotherapy, 2012)
Reviewed by: Rita H. Pierog and students in Education 530 (evening class for teachers-GroupProcess and Theory).